SEGAE: An online serious game to learn agroecology. (June 2021) - Jouan, Julia; Carof, Matthieu; Baccar, Rim; Bareille, Nathalie; Bastian, Suzanne; Brogna, Delphine; Burgio, Giovanni; Couvreur, Sébastien; Cupiał, Michał; Dufrêne, Marc; Dumont, Benjamin; Gontier, Philippe; et al.
Abstract: CONTEXT: There is growing evidence that agroecology can reconcile the environmental, economic, and social pillars of agricultural sustainability. However, teaching and learning agroecology is challenging, especially since most agricultural graduate programs in Europe are not adapted to teach the diversity of its related practices. OBJECTIVE: To improve agroecology learning, we built the online simulation game SEGAE. This article illustrates the game's relevance for learning agroecology. METHODS: The game is based on a modeling framework that gamifies the implementation of agroecological practices in an integrated crop-livestock farm and assesses their impacts on sustainability. To do so, SEGAE is based on an output-oriented approach that represents impacts of practices on various indicators. These impacts are included in a matrix, which is associated with a dynamic graphical interface accessible to players. Two examples of game sessions were developed to illustrate the game's potential. RESULTS AND CONCLUSIONS: In the first example, players can gain knowledge about agroecological practices by implementing practices that improve soil quality and assessing their impacts on sustainability. Results of this example place the farm's improved overall sustainability into perspective with its reduced food production potential. In the second example, players can improve their skills in transition management and acquire a systems approach by converting the farm to organic farming within five years. Results of this example prompt discussion of the steps needed to obtain organic certification and the coherence between crop and animal production needed to foster sustainability. SIGNIFICANCE: SEGAE was designed to strengthen European training in agroecology, and active contributions from users would help to improve this tool, extend it to new farming systems and forge connections within the community of teachers working on agroecology. Graphical abstract: Unlabelled Image Highlights: Agroecology can improve agricultural sustainability but teaching and learning agroecology is challenging This article presents an online simulation game built to improve agroecology learning, SEGAE, and illustrates its potential SEGAE can prompt discussion on steps and trade-offs when increasing sustainability in an integrated crop-livestock farm SEGAE helps to acquire a systems approach and improve skills in agroecological transition management SEGAE was designed to strengthen training in agroecology, and active contributions from users can help to improve this tool